Hierarchical target-driven visual navigation in indoor environment - Zhu, Hongrun (Nanyang Technological University, 2022)
Navigation problem plays an important role in the field of artificial intelligence. In order to navigate the agent to a specific location efficiently, most researches take map information, relative distance towards the target or other prior information as input. Instead, this dissertation is target-driven navigation with only RGB images as input. To address this challenge, we decompose it into two subtasks: object-search and point-navigation. The agent first executes object-search task until the target object is detected, and then executes point-navigation task to reach the target.